Front crawl technical characterization of 11- to 13-year-old swimmers - Silva, A.; Figueiredo, P.; Soares, S.; Seifert, L.; Vilas-Boas, J. P.; Fernandes, R. J. (Pediatric Exercise Science, 2012)
Our aim was to characterize front crawl swimming performed at very high intensity by young practitioners. 114 swimmers 11-13 years old performed 25 m front crawl swimming at 50 m pace. Two underwater cameras was used to assess general biomechanical parameters (velocity, stroke rate, stroke length and stroke index) and interarm coordination (Index of Coordination), being also identified each front crawl stroke phase. Swimmers presented lower values in all biomechanical parameters than data presented in studies conducted with older swimmers, having the postpubertal group closest values to adult literature due to their superior anthropometric and maturational characteristics. Boys showed higher velocity and stroke index than girls (as reported for elite swimmers), but higher stroke rate than girls (in opposition to what is described for adults). In addition, when considering the total sample, a higher relationship was observed between velocity and stroke length (than with stroke rate), indicating that improving stroke length is a fundamental skill to develop in these ages. Furthermore, only catch-up coordination mode was adopted (being evident a lag time between propulsion of the arms), and the catch and the pull phases presented the highest and smallest durations, respectively.